Occult tuberculous postpneumonectomy space empyema four years after lung resection. Issue 789 (July 1991) - Rogiers, P.; Verschakelen, J.; Knockaert, D.; Vanneste, S.
Abstract : We describe a patient in whom a tuberculous postpneumonectomy empyema developed 4 years after resection for lung cancer. The clinical presentation was dominated by non-specific constitutional symptoms, without any chest complaints. A computed tomographic scan of the chest suggested inflammation in the postpneumonectomy space. Ultimately Mycobacterium tuberculosis was cultured from material aspirated by needle thoracocentesis. To our knowledge this is the first report of a tuberculous postpneumonectomy empyema complicating resection for cancer.